Mesenchymal Stem Cells and Atopic Dermatitis: A Review - Daltro, Sérgio Ricardo Teixeira; Meira, Cássio Santana; Santos, Ivanilson Pimenta; Ribeiro dos Santos, Ricardo; Soares, Milena Botelho Pereira (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem/stromal cells (MSCs) are stromal-derived non-hematopoietic progenitor cells that reside in and can be expanded from various tissues sources of adult and neonatal origin, such as the bone marrow, umbilical cord, umbilical cord blood, adipose tissue, amniotic fluid, placenta, dental pulp and skin. The discovery of the immunosuppressing action of MSCs on T cells has opened new avenues for their use as a therapeutic agent for immune-mediated disorders, including allergies. Atopic dermatitis (AD), a chronic and relapsing skin disorder that affects up to 20% of children and up to 3% of adults worldwide, is characterized by pruritic eczematous lesions, impaired cutaneous barrier function, Th2 type immune hyperactivation and, frequently, elevation of serum immunoglobulin E levels. Although, in the dermatology field, the application of MSCs as a therapeutic agent was initiated using the concept of cell replacement for skin defects and wound healing, accumulating evidence have shown that MSC-mediated immunomodulation can be applicable to the treatment of inflammatory/allergic skin disorders. Here we reviewed the pre-clinical and clinical studies and possible biological mechanisms of MSCs as a therapeutic tool for the treatment of atopic dermatitis.